Cardioprotective effects of high-altitude adaptation in cardiac surgical patients: a retrospective cohort study with propensity score matching - Lei, Li; Liu, Mengxue; Ma, Die; Lei, Xia; Zeng, Si; Li, Peng; Huang, Keli; Lyu, Juanjuan; Lei, Qian (Frontiers in Cardiovascular Medicine, 2024)
Background The cardioprotective effect of remote ischemia preconditioning in clinical studies is inconsistent with experimental results. Adaptation to high-altitude hypoxia has been reported to be cardioprotective in animal experiments. However, the clinical significance of the cardioprotective effect of high-altitude adaptation has not been demonstrated. Methods A retrospective cohort study with propensity score matching was designed to compare the outcomes of cardiac surgery between highlanders and lowlanders in a tertiary teaching hospital. The data of adult cardiac surgical patients from January 2013 to December 2022, were collected for analysis. Patients with cardiopulmonary bypass and cardioplegia were divided into a low-altitude group (<1,500 m) and a high-altitude group (≥1,500 m) based on the altitude of their place of residence. Results Of 3,020 patients, the majority (87.5%) permanently lived in low-altitude regions [495 (435, 688) m], and there were 379 patients (12.5%) in the high-altitude group [2,552 (1,862, 3,478) m]. The 377 highlander patients were matched with lowlander patients at a ratio of 1:1. The high-altitude group exhibited a 44.5% reduction in the incidence of major adverse cardiovascular events (MACEs) compared with the low-altitude group (6.6% vs. 11.9%, P = 0.017). The patients in the moderate high-altitude subgroup (2,500–3,500 m) had the lowest incidence (5.6%) of MACEs among the subgroups. The level of creatinine kinase muscle-brain isoenzymes on the first postoperative morning was lower in the high-altitude group than in the low-altitude group (66.5 [47.9, 89.0] U/L vs. 69.5 [49.3, 96.8] U/L, P = 0.003). Conclusions High-altitude adaptation exhibits clinically significant cardioprotection in cardiac surgical patients.